Penentuan Kandungan Antioksidan dan Fenolik Total dari Infusa Daun Tanaman Famili Myrtaceae Secara Spektrofotometri - Yefrida; Hayatul Isra; Refilda (Departemen Kimia Universitas Andalas, 2022)
Myrtaceae family plants are widely distributed in the tropics. The leaves of this plant have been widely used by the community as a traditional medicine. This study aims to determine the total antioxidant and total phenolic content of the infusion of five types of leaves of the Myrtaceae family, namely bay leaves (Syzygium polyanthum), jambak leaves (Syzygium malaccense), guava leaves (Psidium guajava), water guava leaves (Syzygium aqueum). and duwet leaves (Syzygium cumini). Total antioxidant content was determined using the MPM method and total phenolic content using the Folin Ciocalteau method. The highest total antioxidant content was found in jambak leaf infusion of 122.73 ± 3.10 mg AA/g DW, while the highest total phenolic content was found in guava leaf infusion of 58.84 ± 1.86 mg GAE/g DW.